Supraventricular Tachycardia: From Catheter to Catheter Ablation - Sonia Mishra; Ajay Mishra; Jagdish P Mishra (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2017)
I had a privilege of having a really attentive and good medical student rotating through my cardiology office for a month. One day I explained to her in greater details that in spite of all the tests, devices and everything else, the patient history is still the MOST important aspect of overall medical evaluation of a patient. With this advice, I sent her to go to see a patient of mine admitted to the hospital with palpitations.